Return of State Losses Through State Administrative Instruments : an Effort to Avoid Criminal Liability - Amriyanto, Amriyanto; Andika Adhyaksa; Didith Prahara (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to analyze and give birth to the concept of state financial loss return through state administrative legal instruments and to give birth to a loss recovery model in the form of state financial loss return through compensation claims. This study uses a normative type of research using primary, secondary and tertiary legal materials. Legal materials are obtained through library research, then analyzed with qualitative techniques by drawing conclusions in a deductive way. The result of State financial losses due to unlawful acts, both intentional and negligent, that have implications for corruption crimes are problems that can hinder the growth and continuity of development. The return of state financial losses through criminal law instruments in the form of payment of compensation has failed to recover state financial losses. Enforcement of the criminal law on corruption should be the ultimate remedium, not the premium remedium. The legal instrument of state administration offers the recovery of losses through the return of state financial losses in the form of compensation claims. The instrument was used as an effort to avoid criminal liability, but it was successful in recovering losses. This research is very urgent in giving birth to the concept and model of returning state financial losses for the growth and sustainability of national development